A gravura como meio de comunicação: processo de criação de DJ Oliveira - Goya, Edna de Jesus (2006)
The thesis develops a study about the creation process of DJ Oliveira (Dirso José de Oliveira, from Bragança Paulista, SP, 1932-2005), in an approach of the Genetic Critic of Semiotic base. Painter, muralist and engraver, he had his artistic formation in the Santa Helena Group, São Paulo. He moved to Goiânia in 1959, and became one of the modernist movement and engraving founders. In theory, we try to comprehend how and in which way the artist s gesture drawing configures in work, how it moves, it materializes, it inserts in other movements that involve creation and how it intertwines in doing according to the techniques and materials he uses. For the debate about the cultural matters, a dialogue about the complexity thoughts developed by Edgar Morin is established, mediated in the semiotics by Vincent Colapietro, discussing in Pierce the relationship between the subject and the semiotics and the implications in not considering the subjectivity, in this process, once the semiotics reveals subjects not only as users of symbols, but also as processes and products of semiotics, because, according to this thought, the subject can be a result as well as a transformer and symbol experience agent. In the analyses, the communication process is emphasized, which development, in arte, occurs in two moments: during the process of making and when the work is completed. In the first moment, the process of making occurs in an intrapersonal way, according to the dynamic of symbols, during the creation, and in several ways, guiding himself through the drawing and following his footsteps, as well as the exchanges the artist makes in his historical, technical, artistic, material and cultural contexts to make the work. In the second moment, the process of making occurs in an interpersonal way, by means of the contact of the work with the public. In DJ Oliveira s work, the communication becomes amplified due to factors such as the option for the engraving (which in its multiplicity makes possible the access to a range of people), the production of frescos (which, exhibited in public squares and public places of the city makes easy the access to the work) and the strength of the expressiveness as a way of the spectators involvement. For that, DJ Oliveira s relationships with the spaces of creation are discussed as well the city and his ateliers